2016
DOI: 10.1007/s10995-016-2156-0
|View full text |Cite
|
Sign up to set email alerts
|

The Independent Importance of Pre-pregnancy Weight and Gestational Weight Gain for the Prevention of Large-for Gestational Age Brazilian Newborns

Abstract: Objectives To study the independent effect of pre-pregnancy weight, gestational weight gain (GWG), and other important risk factors on newborn birth weight. Methods Baseline data of 435 adult women and their singletons born between January and February 2012 at a public hospital in Brazil were used. Logistic regression was applied to determine the independent importance of pre-pregnancy weight and GWG for large for gestational age (LGA) newborns. Results Among all mothers, 37.9 % were overweight and obese befor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 43 publications
1
13
0
3
Order By: Relevance
“…The relationships this study found between prepregnancy BMI, GWG and GWG rate are consistent with the findings of some existing studies [21][22][23], including a cohort study located in three provinces in southwest China [24]. A meta-analysis showed that insufficient GWG contributed to a lower risk for LGA while excessive GWG was associated with lower risk for SGA [11].…”
Section: Discussionsupporting
confidence: 90%
“…The relationships this study found between prepregnancy BMI, GWG and GWG rate are consistent with the findings of some existing studies [21][22][23], including a cohort study located in three provinces in southwest China [24]. A meta-analysis showed that insufficient GWG contributed to a lower risk for LGA while excessive GWG was associated with lower risk for SGA [11].…”
Section: Discussionsupporting
confidence: 90%
“…As Individual Participant Data (IPD) from those studies was not available, the degree of departure from the recommendations is unknown. Although the meta-analysis reaffirmed the association between GWG outside the IOM recommendations and adverse pregnancy outcomes [4, 10, 17, 2431], the findings were limited by a lack of adjustment for potential confounders (e.g. gestational age in the analysis for preterm birth), inconsistency in outcome definitions (e.g.…”
Section: Introductionmentioning
confidence: 93%
“…The number of women entering pregnancy with high BMI is increasing [12]. High weight gain in pregnancy occurs in both high-income [1315] and low-income countries [16, 17]. The US-based Institute of Medicine (IOM), among others, has attempted to identify an optimal amount of GWG [1, 2, 1820] and has issued recommendations to support healthcare providers advising women on a healthy amount of weight gain in pregnancy [20].…”
Section: Introductionmentioning
confidence: 99%
“…This prospective cohort study is part of the Predictors of Maternal and Infant Excess Body Weight (PREDI) Study initiated in 2012 in Joinville/SC, Brazil, a larger research project examining the determinants and related health outcomes of excess body weight in mothers and their children. An in‐depth description of the overall study has been published previously (Mastroeni et al, ; Santos et al, ). Briefly, all women over 18 years of age who gave birth to a full‐term singleton (between 37 and 42 weeks of gestation) and who did not follow any specific type of diet before or during pregnancy or at the time of delivery were invited to participate.…”
Section: Methodsmentioning
confidence: 99%